Усан дахь кластер бүтцийн амьдрах насыг үнэлэх асуудалд - Ш, Мөнхжаргал; Ч, Баярхүү (Scientific transaction of the National University of Mongolia. Physics, 2022)
The dynamics of liquid water have been investigated experimental on the molecular level by the scattering light. It is shown that there the scattering light quantity associated with optical nonhomogeneous molecular structures in water. The life time of the nonhomogeneous structures is analysed by the Fourier method.